EFFECTIVITY OF DRYING METHODS TO MINIMIZE AFLATOXIN OF DRIED NUTMEG - Sembiring, Bagem BR.; Supriadi, Supriadi; Ediningsih, Ediningsih (Jurnal Penelitian Tanaman Industri, 2020)
Indonesian nutmeg export is constrained due to aflatoxin content that exceeds the minimum limit. This study was aimed at examining the effectiveness of three drying types of nutmeg to diminish aflatoxin contamination. The three drying types tested were (a) the rack type house with a source of solar energy heat combined with a kerosene stove fire, (b) the drying bases one meter above the ground with or without a black cloth cover, and (c) the floor drying 5 cm above the ground with or without black cloth cover. Unpeeled nutmegs were dried in the drying racks until they dried (sound when shaken by hand). After that they were. peeled and redried in the same type of dryer. Observation parameters included temperature, humidity, drying time, moisture content, oil content, oleoresin, myristicin, and aflatoxin content. The results showed that the drying time in the house-type drying rack was 51.5 hours, longer than the para-para and drying floor (30 hours). The temperature during drying in the drying house was 35.6-37.310C lower than the other two types of dryers. However, its humidity was the highest (40.71-49.33%). The moisture content of shelled nutmegs and peeled nutmegs from all drying types fulfill the requirements (< 10%). The total aflatoxin contamination in shelled nutmegs and peeled nutmegs was < 3.28 Âµg/kg, while B1 aflatoxin was < 1.06 Âµg/kg, so that they fulfilled SNI standard. All three drying types can be recommended to be tested further in field scale.Keywords: Nutmeg, Myristica fragrans, drying technology, seed quality.